2008
DOI: 10.1080/00343400701291542
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Patterns of Production Linkages in the Context of Europe's Small Towns: How Are Rural Firms Linked to the Local Economy?

Abstract: Courtney P., Lépicier D. and Schmitt B. Spatial patterns of production linkages in the context of Europe's small towns: how are rural firms linked to the local economy?, Regional Studies. Small towns have received increasing attention from policy-makers aiming to stimulate rural development through territorial approaches. However, it cannot be assumed that fostering local business growth will help generate local economic development either through economies of agglomeration or through spillover effects into su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 27 publications
0
36
0
2
Order By: Relevance
“…Since the 1980s, some of them have experienced socio‐demographic and economic renaissance (OECD ; Kelly & Ilbery ; Bollman & Bryden ), due to the strengthening of small and medium‐sized towns in rural areas (Courtney et al . ) and diffusion of SMEs networks out of large cities (Piore & Sabel ; Brusco ; Becattini ). Improvement in physical infrastructures (Agarwal et al .…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1980s, some of them have experienced socio‐demographic and economic renaissance (OECD ; Kelly & Ilbery ; Bollman & Bryden ), due to the strengthening of small and medium‐sized towns in rural areas (Courtney et al . ) and diffusion of SMEs networks out of large cities (Piore & Sabel ; Brusco ; Becattini ). Improvement in physical infrastructures (Agarwal et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, these enterprises may source locally to reduce their transaction costs or to stay loyal to local suppliers and networks to the detriment of purchasing costs. Courtney et al (2008) found that the more traditional the firm is (ie. smaller, older, lower labour productivity) the more strongly integrated into the local economy.…”
mentioning
confidence: 99%
“…According to Courtney et al (2008) the sectorial profile of the enterprise is decisive for its spatial behaviour. While firms belonging to construction or producer service sectors show strong connectivity to local (input) markets, manufacturing firms are more often linked to the wider economy, their partners come frequently from the regional markets and they often sell their products in the regional or international economy.…”
mentioning
confidence: 99%
“…Furthermore, several endogenous and exogenous factors have resulted in the uneven development of rural economies throughout Europe, leading not only to disparities, but also to the decline of small and medium towns as thriving economic and service centers (Courtney et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, several endogenous and exogenous factors have resulted in the uneven development of rural economies throughout Europe, leading not only to disparities, but also to the decline of small and medium towns as thriving economic and service centers (Courtney et al 2009). This is because the answer to globalization and growing global trade is local development based on the formation of local production networks, exchange, and cooperation at a local level, as well as the general efficiency of the local development environment (Cabus 2001;Christofakis & Tsampra 2012).…”
Section: Introductionmentioning
confidence: 99%